From classical social network theory to social networks on the Internet and virtual communities (Islas, 2024)
Introduction: The current social networking sites on the Internet validate the classical theory of social networks and audience studies that originated at the beginning of the last century. The new sociability that emerges on these platforms poses a challenge for local newspapers. Methods: This research is a descriptive study from a qualitative approach, based on a    bibliographic review of the categories of social networks and participation. In addition to the bibliographic-documentary method, an analysis of Facebook statistics was carried out.Results: Facebook enhances user interactivity through reactions to posts, comments, and the ability to share. Users interact when messages satisfy their needs and establish an emotional connection with them.Conclusions: The classical theory of social networks, specifically the first multidisciplinary intersection with communication theory, produced results that, almost a century later, explain how the digital social networking site Facebook operates. Its algorithm personalizes content, taking into account personal interests and individual mediations.
Keywords: digital social networking sites; virtual communities; interaction; participation